Interdepartmental Interdependence and Coordination: The Case of the Design/Manufacturing Interface - Adler, Paul S. (Organization Science, 1995)
In contrast with the relative stability of interdepartmental coordination mechanisms in ongoing operations, coordination tasks and mechanisms typically change over the course of the product development project’s life cycle. This article presents a taxonomy of these project coordination mechanisms. The taxonomy is based on an inductive analysis of development projects in nine printed circuit board operations and four aircraft hydraulic tubing operations. It distinguishes four modes of interdepartmental interaction—standards, schedules, mutual adaptation and teams (as in Thompson [Thompson, J. D. 1967. Organizations in Action. McGraw-Hill, New York.] and Van de Ven et al. [Van de Ven, A. H., A. L. Delbecq, R. Koenig, Jr. 1976. Determinants of coordination modes within organizations. Amer. Sociological Rev. 41322–338.])—in each of three temporal phases: pre-project, product and process design, and manufacturing. Each of the resulting twelve matrix cells represents a distinct coordination mechanism. Since the objective of coordinating design and manufacturing departments is to ensure an acceptable fit between product design and manufacturing process parameters, the most efficient interdepartmental coordination mechanism is that which is able to deal with the uncertainty of this product/process fit at least cost to the organization. Extending Perrow’s (Perrow, C. 1967. A framework for the comparative analysis of organizations. Amer. Sociological Rev. 32 194–208.) analysis of the two dimensions of uncertainty to the case of product/process fit, the choice of interaction mode within each project phase is hypothesized to depend on the novelty of the product/process fit problem, and the relative importance of coordination effort across the three project phases is hypothesized to depend on the analyzability of the product/process fit problem.